Evaluation context role on generating online product recommendations - Rodrigues, Gustavo Viegas; Quevedo-Silva, Filipe; Freire, Otavio Bandeira De Lamônica; Lopes, Evandro Luiz (Revista de Administração da UFSM, 2020)
This article aims at contributing to Construal Level Theory research, complementing Wien and Olsen (2012) work relating interpretation context with services’ perceived quality, satisfaction and recommendation. By applying online questionnaires on 690 respondents and using structural equation modeling, authors have corroborated Wien and Olsen’ model for e-commerce environment, regardless of product category. Further studies could amplify the analysis of online environments, including the development of a specific and proper scale.